ANALISIS AUDIT SYARIAH, AKUNTABILITAS DAN TRANSPARANSI PADA ORGANISASI PENGELOLA ZAKAT DALAM MEMAKSIMALKAN POTENSI ZAKAT - Ghoriyyudin, Aghry; Fitriana, Fitriana; Santoso, Rachmat Agus; Devi, Rini Fitrianti (LPPM Universitas Bina Bangsa, 2024)
Indonesia has a majority Muslim population. This is a great potential especially for the Islamic and national economy, especially zakat. But unfortunately, the enormous potential of zakat still cannot be maximized. Of the total zakat potential of Rp. 327 trillion annually, only Rp. 40 trillion is realized. One of the factors is the low trust of muzakki to OPZ (Zakat Management Organization). To increase zakat revenue, it is necessary to take several strategic steps that can increase zakat revenue such as sharia audits, accountability and transparency carried out by OPZ. This research aims to find out and review previous research on the relationship between sharia audits, accountability and transparency in maximizing zakat potential. This research uses qualitative method with literature study approach which is to strengthen the argument with information collected from articles published in national journals. The researcher took 21 samples of sinta indexed articles sourced from google schoolar. This study found that based on the results of previous research mapping, many have proven that sharia audit, accountability and transparency of the Organization of Zakat Management (OPZ) have an impact on zakat revenue and have an important role in increasing public trust in OPZ. Out of 21 articles, there are only 2 articles that conclude accountability has no effect on public trust and interest in paying muzakki. Researchers hope that there will be further research that is more in-depth related to the potential of zakat that has not been maximized, because researchers use sample data that is still limited